2009
DOI: 10.1002/maco.200805074
|View full text |Cite
|
Sign up to set email alerts
|

The corrosion and electrochemical behavior of pure aluminum in additive‐containing alkaline methanol–water mixed solutions

Abstract: The corrosion and electrochemical behavior of aluminum in inhibited and uninhibited 4 M KOH-methanol-water mixed solutions with a methanol/water volume ratio of 3:2 were investigated by means of hydrogen collection, polarization curve, galvanostatic discharge, and electrochemical impedance spectroscopy (EIS). The results of hydrogen collection and electrochemical experiments showed that the addition of ZnO can obviously inhibit the corrosion of aluminum in the 4 M KOH-methanol-water solutions, and its inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 24 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…This performance took place using both Zn additives. The higher inhibition properties of the ZnO vs. ZnCl 2 could be explained by the fact that the ZnO reacted to the zincate form in the highly alkaline solution to form the Zn cover, as described by Wang et al [22]:…”
Section: Resultsmentioning
confidence: 92%
“…This performance took place using both Zn additives. The higher inhibition properties of the ZnO vs. ZnCl 2 could be explained by the fact that the ZnO reacted to the zincate form in the highly alkaline solution to form the Zn cover, as described by Wang et al [22]:…”
Section: Resultsmentioning
confidence: 92%
“…Methanol offers excellent corrosion inhibition in an alkaline solution (Wang et al, 2007(Wang et al, , 2009. Earlier, methanol was applied as an anolyte in dual-electrolyte AABs (Wang et al, 2014;Teabnamang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that ZnO reduces Al corrosion rate, while it does not affect the anodic characteristic (current density and over-potential) of Al [35]. Much weaker inhibition effect than ZnO was established with polyaniline [36], methanol [37], hydroxytryptamine [38] dimethyl amine epoxy propane [39] and sodium silicate [40]. It was also reported that the protection effect of these inhibitors might be improved by the addition of haloidions to the alkaline solution [41].…”
Section: Introductionmentioning
confidence: 91%